EFFECT OF SILICATE ON THE GROWTH AND ION UPTAKE IN NaCI-TRESSED PLANTS - Didy Sopandie; Masumi Moritsugu; Toshio Kawasaki (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1995)
The purpose of this experiment was to investigate the effect of Si on the growth and ions uptake (K, Na, Ca, and Mg) in rice, bean and barley plants grown in saline conditions. Rice and bean plants were subjected to 0 and 30 mM NaCI in the nutrient solution with and without Si, whilst for barley plants 0 and 40 mM NaCI were used. In this investigation, 2.0 mM Si was used as silicilic acid. The results revealed that Si had the protective effect on salt injury only for rice plants. This alleviating effect of Si appeared to be associated with the interference of Si on the upward Na transport by reducing the content of Na in the shoots and retaining it in the roots. Generally, addition of Si did not affect the content of K in all plants tested. Except for rice, Si had no or less effect on Ca and Mg uptake in bean and barley plants.